2(4y-3)=3(y+5)

Simple and best practice solution for 2(4y-3)=3(y+5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(4y-3)=3(y+5) equation:


Simplifying
2(4y + -3) = 3(y + 5)

Reorder the terms:
2(-3 + 4y) = 3(y + 5)
(-3 * 2 + 4y * 2) = 3(y + 5)
(-6 + 8y) = 3(y + 5)

Reorder the terms:
-6 + 8y = 3(5 + y)
-6 + 8y = (5 * 3 + y * 3)
-6 + 8y = (15 + 3y)

Solving
-6 + 8y = 15 + 3y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-3y' to each side of the equation.
-6 + 8y + -3y = 15 + 3y + -3y

Combine like terms: 8y + -3y = 5y
-6 + 5y = 15 + 3y + -3y

Combine like terms: 3y + -3y = 0
-6 + 5y = 15 + 0
-6 + 5y = 15

Add '6' to each side of the equation.
-6 + 6 + 5y = 15 + 6

Combine like terms: -6 + 6 = 0
0 + 5y = 15 + 6
5y = 15 + 6

Combine like terms: 15 + 6 = 21
5y = 21

Divide each side by '5'.
y = 4.2

Simplifying
y = 4.2

See similar equations:

| 2x+57=33findx | | u+3.14=70 | | 2x+57=33 | | (x+2i)(x-2i)(x+4)=0 | | 6=J-5 | | 3y+7=2x-5 | | N/10-20=20 | | 100x-40y=320 | | 6x7/8= | | 3z+5z=0.6 | | (n)(n)+72=-17n | | 3x-5=6+x | | 6x+7=3(2x+4) | | (k)(k)-11k+30=0 | | (12y)(12y)+40y=7 | | 3x^2-8+5x=0 | | 3x+6=507 | | 10/3x1/2 | | 6d+4=-32 | | 5/6z=5/7 | | 18/sin40 | | a=bd | | p^2-14p=51 | | (d)(d)=5d | | 10c/2-32/4=56/8 | | (w)(w)=12 | | 3/7x1/7 | | 6-9(1-7n)=-21 | | -4x-16y=-12 | | 2y=-5x-3 | | (2x+8)+(3x-4)+x= | | 8(x+9)=72 |

Equations solver categories